Waning immunity to plasma-derived hepatitis B vaccine and the need for boosters 15 years after neonatal vaccination - Chun‐Yi Lu; Bor‐Luen Chiang; Woo Chi; Mei‐Hwei Chang; Yen‐Hsuan Ni; Hsu–Mei Hsu; Shiing–Jer Twu; Ih‐Jen Su; Li‐Min Huang; Chin‐Yun Lee (2004)
Neonatal immunization with hepatitis B (HB) vaccine is highly effective; however, more needs to be learned about the duration of protection and indications for boosters. We measured antibody to HB core antigen (anti–HBc), HB surface antigen (HBsAg), and pre– and postbooster titers of HBsAg antibody (anti–HBs) 15 years after primary neonatal immunization with plasma–derived HB vaccines in 2 cohorts of 15–year–old children. Group A consisted of 78 children who were born to HB e antigen-positive HBsAg carrier mothers and had developed protective levels of anti–HBs antibodies (≥10 mIU/mL) following HB immunization. Group B consisted of 113 apparently healthy children whose anti–HBs titers after vaccination were unknown. Anti–HBs was undetectable (antibody titer <10 mIU/mL) in 29.9% in group A and 62.4% in group B ( P < .001). Anti–HBc was detected in 33.3 % in group A and 4.4 % in group B ( P < .001). After a single booster dose of HB vaccine, 2.7% in group A and 3.3% in group B remained anti–HBs-negative. A blunted serological response was noted in approximately 20% in both groups. One HBsAg carrier was detected in group A (1.3%) and 4 in group B (3.5%). Fifteen years after neonatal immunization with plasma–derived HB vaccine, a large proportion of children exhibited waning immunity. This poses the risk of breakthrough infection. A single booster augmented the serological response to the vaccine in most but not all subjects. In conclusion , our findings suggest that one or more booster immunizations are needed in seronegative subjects by at least 15 years following neonatal immunization with plasma–derived HB vaccine. (Hepatology 2004;40:1415-1420.)